2009
DOI: 10.1155/2009/674801
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Acute Lymphoblastic Leukemia Subtypes in Moroccan Children

Abstract: We present the incidence and the immunologic characteristics of acute lymphoblastic leukemia (ALL) subsets in Moroccan children. We studied 279 unselected patients below the age of 18 years with newly diagnosed ALL. Cases were classified according to immunophenotype: 216 (77.42%) precursor B-cell phenotype (pB-cell), mature B-cell in 4 (1.43%), and T-cell in 59 (21.15%) cases. The subclassification using the CD10 antibody revealed 197 cases pB-ALL CD10+ (91.2%) and 9 cases T-ALL CD10+ (19.2%). The age distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
30
2
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 27 publications
(41 reference statements)
19
30
2
2
Order By: Relevance
“…16,18,19 In this study, ALL incidence was observed more in male gender (M: F= 1.3:1) matching the finding of further studies, whereas it reached 1.84:1 in others. 11,15,[20][21][22] The commonest complaint of the study patients was fever, followed by bone pain, weight loss, and fatigability, these were consistent with findings by other studies. 23,24 Bone pain was presented in 22 patients (40%), it was variably reported by many studies (19-67%), Joint pain was present in one (1.8%) patient only (ankle joint), whereas it was presented more (6-9.3%) by other studies.…”
Section: Discussionsupporting
confidence: 90%
“…16,18,19 In this study, ALL incidence was observed more in male gender (M: F= 1.3:1) matching the finding of further studies, whereas it reached 1.84:1 in others. 11,15,[20][21][22] The commonest complaint of the study patients was fever, followed by bone pain, weight loss, and fatigability, these were consistent with findings by other studies. 23,24 Bone pain was presented in 22 patients (40%), it was variably reported by many studies (19-67%), Joint pain was present in one (1.8%) patient only (ankle joint), whereas it was presented more (6-9.3%) by other studies.…”
Section: Discussionsupporting
confidence: 90%
“…Immunophenotypic criteria of B-ALL All our B-ALL cases express CD19 while TdT was expressed in 97.4% and this found to be similar to Bachir et al [25]. In B-ALL, myeloid aberrant phenotype has been …”
Section: Leukemia Subtypessupporting
confidence: 87%
“…Positivity of CD3 was 38.5% and like some previous studies was not confirmed as the most sensitive marker, which is limited by the fact that it is uncommonly expressed on the surface of T-ALL and is almost always present abundantly in the cytoplasm of these cells [13]. All T-ALL cases in this study were negative for HLADR and this incidence is much higher than reported elsewhere [13,25] which may be explained by low number of cases in our study. Regarding aberrant B-cell marker expression on T-ALL, it was reported that CD10 and CD19 are expressed in various percentages on such cases (19-43% and 0-2.3%, respectively) [13,19].…”
Section: Immunophenotypic Criteria Of T-allcontrasting
confidence: 84%
“…Our study confirmed that early pre-B ALL lack cytoplasmic and surface immunoglobulin and Kappa and Lambda while pre-B exhibit cytoplasmic immunoglobulin which agreed with Fatima Bachir et al study that indicated the same result [16].…”
Section: Discussionsupporting
confidence: 91%
“…This result concordant with Fatima Bachir et al that showed 100% of cases with surface Ig (lambda/kappa) and this emphasizes the importance of immunoglobulin and light chain testing in B-ALL for sub classification [16].…”
Section: Discussionsupporting
confidence: 90%